Earnings Management Indications in Late Financial Reporting: Evidence from Consumer Cyclicals Sector Companies on the Indonesia Stock Exchange - Indri Erani; Tri Joko Prasetyo; Chara Pratami Tidespania Tubarad (Global Academy of Business Studies, 2026)
Purpose: This study aims to investigate whether earnings management, as measured by the Beneish M-Score, differs significantly between on-time and late-reporting consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX). Research Methodology: A quantitative comparative design was employed using 76 firm-year observations (38 on-time and 38 late reporters) from 2020 to 2024. Timeliness was classified based on the OJK regulatory deadline, and earnings management was measured using the eight-component Beneish M-score. The Mann-Whitney U test was used for hypothesis testing, and robustness was assessed via logarithmic data transformation. Results: Late reporters had significantly higher aggregate M-scores (p < 0.05), with 86.84% classified as likely manipulators, compared to 63.16% of on-time reporters. Descriptive trends showed higher DSRI, GMI, TATA, and LVGI in late reporters, although no significant differences were observed in the individual components. TATA became significant after logarithmic transformation, indicating its sensitivity to distributional adjustments. Conclusions: The findings suggest a strong association between delayed reporting and earnings-manipulation risk. Regulators, auditors, and investors should use the Beneish M-Score as an early warning indicator of potential earnings management in companies that report late. Limitations: The sample is limited to the consumer cyclicals sector, and the Beneish M-score captures only accrual-based earnings management. The binary classification of reporting timeliness may overlook the varying degrees of delay. Contributions: This study provides new empirical evidence on the relationship between financial reporting timeliness and earnings quality in Indonesia, offering insights for market practitioners and regulators.